Characterization of Herpes Simplex Virus Type 1 RNA Present in the Absence of De Novo Protein Synthesis - Anderson, Kevin P. (1980)
We used herpes simplex virus type 1 (HSV-1) DNA and restriction fragments of HSV-1 DNA covalently coupled to cellulose as a reagent to isolate for further characterization the major and minor HSV-1 immediate-early mRNA species in HeLa cells infected and maintained in the absence of de novo protein synthesis. Five major and several minor immediate-early mRNA species were characterized. One major species was a 4.2-kilobase mRNA mapping in the TR(S)/IR(S) region with its 3′ end distal to the U(S) region; this mRNA encoded a 170,000-dalton polypeptide in vitro. A 2.8-kilobase mRNA, encoding a 120,000-dalton polypeptide, was mapped in the TR(L)/IR(L) region with its 3′ end directed toward the U(L) region. Three 1.8-kilobase mRNA species were mapped. One, mapping in the IR(S) region with its 3′ end in the U(S), encoded a 68,000-dalton polypeptide. One mapped in the TR(S) region and had its 3′ end in the U(S) region; the third one encoded a 64,000-dalton polypeptide and mapped in the U(L) region near the IR(L) region. One minor species 5.2 kilobases in size was clearly detectable mapping in the U(L) region. Furthermore, there were indications that one or more immediate-early mRNA species approximately 3 kilobases in size hybridized to regions near the TR(L) and in or near the TR(S)/IR(S) regions. Nuclear immediate-early RNA mapped only in those regions where polyribosomal immediate-early mRNA mapped, although minor differences were seen. Finally, we demonstrated that at least three major immediate-early mRNA's—4.2 kilobases, 2.8 kilobases, and the 1.8-kilobase one mapping in the IR(S)/U(S) region—continued to appear on polyribosomes as functional mRNA late after infection.